Intestinal ciliates (Alveolata, Ciliophora) in Brazilian domestic horses (Equus caballus L.) and a review on the ciliate communities associated with horses around the world - Cedrola, Franciane; Bordim, Suyane; D’agosto, Marta; Dias, Roberto Júnio Pedroso (Zootaxa, 2019)
The aims of this study were to identify and quantify the gastrointestinal ciliates from Brazilian domestic horses, to compare the data obtained with previous studies and to review data on ciliate communities associated with horses around the world. We used eight domestic horses, kept under extensive management. Fecal samples were obtained immediately after defecation of animals and fixed in 18.5% formaldehyde. We identify 24 species of endosymbiotic ciliates, distributed in two subclasses, two orders, five families and 13 genera. The ciliate composition was similar among the animals analyzed. The family Blepharocorythidae presented the higher prevalence and the family Buetschliidae was observed in greater abundance and density. Among the species identified, Cycloposthium dentiferum was observed for the first time in Central and South America and Bundleia elongata, B. inflata, B. piriformis, B. vorax and Cycloposthium psicauda, were observed for the first time in the American continent. In addition, the species Buissonella tapiri, which was originally discovered in fecal contents of the American tapir (Tapirus terrestris) in Brazil was observed for the first time associated to Equus caballus. The review on the ciliate communities associated with horses around the world demonstrated that the equine ciliates are a very diversified group with representatives in two subclasses, Suctoria and Trichostomatia, totaling 78 species distributed in three orders and six families, having been registered in different equine hosts (Equus asinus, Equus caballus and Equus quagga) and geographic locations (USA, China, Russia, Taiwan, Mexico, Cyprus, Turkey, Kyrgyzstan and Brazil).